Game Changer for Tomorrow’s Retail Landscape: The Rise of Community Market - Srivatsan, Muthuswamy (International Journal of Supply Chain and Logistics, 2025)
Purpose: In the rapidly evolving business landscape, and with retailers thinking out of the box to attract new customers and retain their loyal ones, this strategy of "community market" will give ample scope for retail giants to facilitate their customers and provide them with the luxury of saving their valuable time and avoiding the drive in city traffic. We hereby propose this ideation: Community Market, a convenient kiosk that can be planned for every neighborhood or suburb with essential household items, coupled with a payment ecosystem setup to simplify the overall process. Methodology: The "Community Market" concept addresses the growing need for localized, efficient, and accessible retail solutions. In an era where convenience is a driving factor for consumer behavior, these markets provide a practical alternative to large-scale retail stores, often located far from residential areas. By situating kiosks within close proximity to neighborhoods, the community market eliminates the need for long commutes, thus saving time, reducing fuel consumption, and minimizing the environmental impact associated with urban traffic congestion. Findings: The implementation of these kiosks can significantly contribute to the enhancement of urban living standards. By offering essential household goods at strategic locations, the community market ensures that basic necessities are within easy reach of residents. This approach not only meets the immediate needs of consumers but also promotes the concept of micro-retailing, where smaller, strategically placed outlets cater to specific local demands. Furthermore, the integration of a robust payment ecosystem enhances the shopping experience by aligning with modern consumer preferences for cashless and contactless transactions, promoting efficiency and financial inclusion. In addition to convenience, the community market fosters community bonds, supports local producers, reduces the carbon footprint of transportation, and contributes to a sustainable and customer-focused future. With its scalability and adaptability to different regions and demographics, the community market emerges as a transformative model poised to redefine the retail landscape. Unique Contributions to Theory, Policy and Practice: Community Market is a total game changer from the traditional Warehouse Management System models by integrating advanced technologies such as Artificial Intelligence, Predictive Data Analytics. The potential to streamline the Inventory Management by using real time analytics plays a vital role in maintaining high availability of products in shelves and thereby sculpts a way to new theories in Supply Chain space. The instant fulfillment with Community Market contributes to highly satisfied customer experience and improves the position in the competitive retail world. This versatility enables business to shift gears and adapt to customer preferences and dynamics. Community Markets are tactically located in urban communities, which reduces the carbon footprint by minimizing frequent trips to Super Markets, particularly in a highly congested area and dramatically reduces the emission levels.